2022
DOI: 10.1159/000526964
|View full text |Cite
|
Sign up to set email alerts
|

The Glasgow Prognostic Score Predicts Outcomes of Pembrolizumab or Atezolizumab Monotherapy in Patients with Pretreated Non-Small Cell Lung Cancer

Abstract: Introduction: Predictors of the effectiveness of immune checkpoint inhibitor (ICI) monotherapy in previously treated patients with non-small cell lung cancer (NSCLC) remain ill-defined. We investigated whether the Glasgow prognostic score (GPS) could serve as such predictors. Methods: Eighty patients treated with pembrolizumab or atezolizumab monotherapy as second- or subsequent-line therapy for NSCLC were retrospectively reviewed, and the associations between GPS, BMI, and each of progression-free survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In the current study, we found that a high GPS (i.e., CRP ≥1.0 mg/dL and albumin <3.5 g/dL) before the initiation of first-line chemotherapy was significantly associated with early disease progression and mortality in patients with ES-SCLC. While few studies have assessed the correlation between the prognosis of patients with SCLC and the GPS, several have revealed that the modified GPS (mGPS), which is based on serum albumin, CRP, and the GPS, is a prognostic indicator of OS in patients with SCLC [17][18][19][20]. Our study's findings are consistent with those of the abovementioned studies [18][19][20][21]; however, to the best of our knowledge, ours is the first study to assess the relationship between the GPS and the outcomes of chemotherapy in patients with SCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we found that a high GPS (i.e., CRP ≥1.0 mg/dL and albumin <3.5 g/dL) before the initiation of first-line chemotherapy was significantly associated with early disease progression and mortality in patients with ES-SCLC. While few studies have assessed the correlation between the prognosis of patients with SCLC and the GPS, several have revealed that the modified GPS (mGPS), which is based on serum albumin, CRP, and the GPS, is a prognostic indicator of OS in patients with SCLC [17][18][19][20]. Our study's findings are consistent with those of the abovementioned studies [18][19][20][21]; however, to the best of our knowledge, ours is the first study to assess the relationship between the GPS and the outcomes of chemotherapy in patients with SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, CRP is a nonspecific inflammatory marker that is also potentially useful in identifying poor nutritional status and the risk of poor OS [8,9], while albumin is a nutritional marker that is inversely correlated with CRP [10]. The GPS was initially developed by Forrest et al [11] as a prognostic factor for patients with advanced non-SCLC (NSCLC), and many studies have found the GPS to be an independent predictor of survival in patients with various cancers, including NSCLC [12][13][14][15][16][17]. However, reports assessing the correlation between the GPS and efficacy of chemotherapy in patients with ES-SCLC are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with NSCLC frequently experience weight loss and a systemic inflammatory response, which can lead to cancer-associated cachexia [3,4]. The Glasgow prognostic score (GPS) was initially developed by Forrest et al [5] as a prognostic indicator for patients with advanced NSCLC; subsequently, various studies found that the GPS is an independent predictor of survival in patients with various cancers, including NSCLC [6][7][8][9][10][11]. The GPS is an evaluation system that relies on serum C-reactive protein (CRP) and albumin levels to assess systemic inflammatory response.…”
Section: Introductionmentioning
confidence: 99%